CD8(+) T-cell encephalitis mimicking PRES in AIDS: a case report - Ishiguro, Mayu (BMC Neurol, 2020)
BACKGROUND: Diverse mechanisms including infections, autoimmune inflammatory reactions, neoplasms, and degeneration are involved in the central nervous system in cases of acquired immune deficiency syndrome. In such cases, it is difficult to determine the precise pathogenesis by radiological examination and laboratory testing. CASE PRESENTATION: We report a 37-year-old Japanese woman who had untreated hypertension and gender identity disorder and had been taking testosterone injections since she was 19 years old. She developed a headache and visual field deficits together with elevated blood pressure. According to radiological findings, she was initially suspected as having posterior reversible encephalopathy syndrome in the right parieto-occipital lobe with reversible cerebral vasoconstriction syndrome. Human immunodeficiency virus antibody was positive and the CD4(+) T-lymphocyte count was 140 cells/μl. Therefore, antiretroviral therapy was started. Antiretroviral therapy suppressed the activity of acquired immune deficiency syndrome but worsened her visual symptoms and expanding radiological lesions. Brain biopsy led to the diagnosis of CD8(+) encephalitis, and she also fulfilled the diagnosis of paradoxical immune reconstitution inflammatory syndrome. Corticosteroid therapy alleviated her symptoms. CONCLUSIONS: This is a rare case of CD8(+) encephalitis, with an exacerbation owing to paradoxical immune reconstitution inflammatory syndrome after antiretroviral therapy, which radiologically mimicked posterior reversible encephalopathy syndrome. Corticosteroid therapy was effective; thus, it is important to provide a pathological diagnosis in such cases.